Architecture of operational open platform for smart home - Tao GUO; Kai SUN (Dianxin kexue)
In recent years,telecom operators have begun to make strategic transformation and layout to the smart home ecosystem.Telecom operators hope to build a smart home open platform to realize business ecology and intelligent operation,provide users with innovative business models and consumption experience.How to build an open platform for smart home based on the characteristics of operators has become a hot topic in the industry.The architecture mode and the existing problems of the mainstream open platform for smart home were firstly analyzed,then the key elements of open platform of telecom operators were studied.Finally,the key technical direction and application practice was proposed to build the open platform for the operators.